Cooperative Research As a Strategy for University Teacher Training. A Case Study of Lesson and Learning Study - Servan-Núñez, María José; Soto-Gómez, Encarnación; Pérez-Gómez, Ángel Ignacio (My University, 2013)
This paper presents the possibilities offered by Lesson and Learning Studies for training and for improving and generating knowledge by reconstructing the practical knowledge of teachers. Firstly, we provide a summary of the concept of practical knowledge and the tradition of teachers researching their own practice. This is followed by some principles of Lesson and Learning Studies, with examples of their possibilities for university teacher training taken from a case study of our own practice during a university master's degree.
Keywords: Didáctica; Profesores - Formación profesional; Docentes investigadores; Lesson and Learning Studies; Educación superior; Desarrollo profesional docente